Pemberdayaan masyarakat dalam pemanfaatan limbah padat tahu sebagai bahan baku pupuk organik ramah lingkungan - Maharani Kusumaningrum; Nadya Alfa Cahaya Imani; Ria Wulansarie; Vera Noviana Sulistyawan; Indrasukma Permanadewi; Elvina Belva Fithriyah; Berliana Putri Rahmalia; Hidayatul Munadhiroh; Hasna Rifqi Nabila; Anin Bimarhamah (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The tofu industry generates a large amount of solid waste that is often underutilized and may pollute the environment if left unmanaged. "Tahu Siip Bu Pariyem" MSME in Sumurrejo Village, Semarang City, is one of the traditional tofu producers generating approximately 25 kg of solid waste per day. Currently, only a small portion is used as animal feed, while the rest is discarded. In fact, tofu solid waste contains high nutritional content and has potential to be processed into organic fertilizer. This community service program aims to educate and train residents on how to convert tofu waste into environmentally friendly and economically valuable solid organic fertilizer. The implementation methods include identification, socialization, training, action programs, and evaluation. Activities were carried out through counseling, hands-on organic fertilizer production, and digital marketing training. The results show increased knowledge and skills among residents in processing tofu waste, as well as a growing interest in producing and marketing organic fertilizer independently. Therefore, this initiative not only reduces environmental pollution but also offers a community-based circular economy solution. Utilizing tofu waste as organic fertilizer has proven to be an effective and applicable method to support sustainable agriculture and local economic independence.